2023
DOI: 10.3991/ijet.v18i20.42075
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception of Using ChatGPT in Counseling and Mental Health Education: The Benefits and Challenges

Aseel O. Ajlouni,
Abdallah Salem Almahaireh,
Fatima Abd-Alkareem Whaba

Abstract: ChatGPT is an artificial intelligence (AI)-based chatbot that has expanded in popularity among users in several fields. It could transform education and support achieving sustainable development goals. Providing counseling and mental health services is a vital national goal for maintaining sustainable goals. As evidence of innovative technology’s ability to support sustainability in the digital era, no study has been found to investigate ChatGPT in counseling and mental health education based on students’ perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
(87 reference statements)
1
0
0
Order By: Relevance
“…Specifically, our results show that they perceived the robotic coach was perpetuating social stereotypes and biases such as gender stereotypes. These findings are in line with a previous study in which undergraduate students interacted with ChatGPT in Arabic language, and ChatGPT generated data in the context of counseling and mental health was not suitable for Arabic society, customs, traditions, and culture [36]. This could have been attributed to the bias in the training data as reported previously in a study that focused on bias of ChatGPT in American society [37].…”
Section: Discussionsupporting
confidence: 90%
“…Specifically, our results show that they perceived the robotic coach was perpetuating social stereotypes and biases such as gender stereotypes. These findings are in line with a previous study in which undergraduate students interacted with ChatGPT in Arabic language, and ChatGPT generated data in the context of counseling and mental health was not suitable for Arabic society, customs, traditions, and culture [36]. This could have been attributed to the bias in the training data as reported previously in a study that focused on bias of ChatGPT in American society [37].…”
Section: Discussionsupporting
confidence: 90%
“…An examination of the collected information showed that students had a favorable opinion of using ChatGPT. Nevertheless, students' experiences utilizing ChatGPT in the counseling and mental health education domains have not yet been extensively covered in the scholarly literature on ChatGPT (Ajlouni et al, 2023).…”
Section: Perceptions Of Chatgpt As a Digital Co-educatormentioning
confidence: 99%
“…ChatGPT exhibits signi cant potential in the eld of education by giving students access to tutoring and support, enabling customized learning, delivering research help, and elevating student engagement (Ajlouni et al, 2023;Biswas, 2023). Furthermore, ChatGPT responds to certain queries, makes information retrieval easier, and helps with code generation, computations, and statistical analysis (Halaweh, 2023).…”
Section: Perceptions Of Chatgpt As a Digital Co-educatormentioning
confidence: 99%
See 1 more Smart Citation
“…ChatGPT has been used as a part of a collaborative design framework to simulate the human design process and it was received positively by participants [5]. Similarly, A survey study in the field of mental health shows that respondents perceive ChatGPT as a beneficial learning tool [6]. A questionnaire study of university students shows that ChatGPT is viewed in a positive manner [7].…”
Section: Introductionmentioning
confidence: 99%